2019
DOI: 10.1002/aur.2091
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Breastfeeding Initiation and Duration and Autism Spectrum Disorder in Preschool Children Enrolled in the Study to Explore Early Development

Abstract: Studies report inconsistent findings on the relationship between ASD and breastfeeding. We explored associations between ASD and breastfeeding initiation (yes/no) and duration (months categorized in tertiles) in the Study to Explore Early Development, a community-based case-control study in six sites in the Unites States. We adjusted for various child and mother demographic and pregnancy factors. Breastfeeding initiation was reported in 85.7% of mothers of children with ASD and 90.6% of mothers of controls. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 72 publications
3
25
1
4
Order By: Relevance
“…[ 5 , 6 ], and previous studies have identified the role of breastfeeding in neurodevelopment among newborns [ 7 , 8 , 9 , 10 ]. However, the associations between breastfeeding and ASD have remained unclear ( Table S1 in Supplementary Materials) [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Although the latest meta-analyses of 13 studies provided evidence that breastfeeding may protect against ASD [ 32 ], several newly published studies were not included, providing additional information with inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 , 6 ], and previous studies have identified the role of breastfeeding in neurodevelopment among newborns [ 7 , 8 , 9 , 10 ]. However, the associations between breastfeeding and ASD have remained unclear ( Table S1 in Supplementary Materials) [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Although the latest meta-analyses of 13 studies provided evidence that breastfeeding may protect against ASD [ 32 ], several newly published studies were not included, providing additional information with inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
“…In a case-control study evaluating the association between breastfeeding and ASD, the absence of breastfeeding when compared to breastfeeding for more than six months was associated with a significant increase in the risk of ASD (OR=2.48, %95 CI=1.42-4.35) [54]. Besides, in a study by Soke et al [55], the reported mean breastfeeding duration of the children with ASD was 7.3±7.2 months and that of control children was 9.3±7.2 months. In another study, Boucher et al [56] reported that the mean breastfeeding duration in the children with ASD was 6.9±5.1 months.…”
Section: Discussionmentioning
confidence: 96%
“…[ 39 ], reported that maternal high-fat diet during pregnancy can cause microbial dysbiosis, which may increase the probability that the neonate may undergo ASD. Studies also have indicated that breast-feeding decreases the risk of developing ASD, while formula-feeding increases the abundance of Clostridium difficile in the infant's gut, which is associated with higher risk of ASD [ 40 , 41 , 42 ].…”
Section: Gut Microbiotamentioning
confidence: 99%